(untitled) (Biocenosis, 2012)
University of Medical Sciences (UCIMED) is making efforts to generate the development of environmental awareness and a responsible attitude to the environment. For this has taken actions, such as performing field trips and community university job (TCU). In the context of the university community were initiated several programs, among them: recovery of recyclable waste, smoke-free campus, reducing power and water consumption.